Continuity and Change of Silat Pelintau as a Cultural Heritage of the Tamiang Community in Aceh Tamiang Regency - Elisa, Elisa; Purba, Mauly; Heniwati, Yusnizar (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2024)
Silat Pelintau is a traditional art of the Tamiang Malay ethnic community which originates from local wisdom and then became a performing art and underwent changes in function and use. Specifically, this research aims to determine the exact continuity and changes of Silat Pelintau in the Tamiang Malay community over several periods in Aceh Tamiang Regency. The research method used is descriptive qualitative. The continuity and changes of silat pelintau in the Tamiang Malay Ethnic community have connected periods within a certain period of time up to the present. The continuity of Silat Pelintau itself starts from colonialism, independence, the New Order, and up to the present.